2017
DOI: 10.1136/bmjopen-2017-017399
|View full text |Cite
|
Sign up to set email alerts
|

EntericSalmonellain humans and food in the Middle East and North Africa: protocol of a systematic review

Abstract: IntroductionNon-typhoidal Salmonella is considered one of the leading causes of foodborne disease worldwide. This protocol provides methods that will be used to synthesise available epidemiological data on non-typhoidal enteric Salmonella in humans and food in Middle East and North Africa (MENA) region and to characterise the morbidity of human salmonellosis in this region.Methods and analysisA systematic review will be conducted based on the Cochrane Collaboration handbook and will be reported following the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(13 reference statements)
0
2
0
1
Order By: Relevance
“…This systematic review, informed by the Cochrane Collaboration handbook (Higgins & Green, 2011), was reported following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines (Table S1; Moher, Liberati, Tetzlaff, & Altman, 2010) and the Meta-analyses Of Observational Studies in Epidemiology (MOOSE) checklist (Table S2; Stroup et al, 2000). A priori peer-reviewed protocol for this review has been registered in PROSPERO (CRD42016046360) and published elsewhere (Chaabna & Alali, 2017). Minor amendments were implemented across this review, whenever was needed.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…This systematic review, informed by the Cochrane Collaboration handbook (Higgins & Green, 2011), was reported following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines (Table S1; Moher, Liberati, Tetzlaff, & Altman, 2010) and the Meta-analyses Of Observational Studies in Epidemiology (MOOSE) checklist (Table S2; Stroup et al, 2000). A priori peer-reviewed protocol for this review has been registered in PROSPERO (CRD42016046360) and published elsewhere (Chaabna & Alali, 2017). Minor amendments were implemented across this review, whenever was needed.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…Details of the search strategy have been published [ 7 ]. Similar search criteria have been utilized for SRs on PH in MENA and published in peer-reviewed journals [ 10 , 20 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Los agentes causantes de ETAS son los organismos tifoideos (causantes de la enfermedad conocida como Fiebre Tifoidea) que agrupan a los serovares Typhi y Paratyphi (Crump et al, 2015). La OMS estima que anualmente ocurren aproximadamente 78.7 millones de casos de ETAs en el mundo con 59 000 muertes asociadas solo a este organismo (Chaabna & Alali, 2017).…”
Section: Organismos Bacterianosunclassified